2021
DOI: 10.3390/ijerph182312663
|View full text |Cite
|
Sign up to set email alerts
|

Using an Integrated Social Cognition Model to Explain Green Purchasing Behavior among Adolescents

Abstract: Strengthening pro-environmental behaviors such as green purchasing behavior is important for environmental sustainability. An integrated social cognition model which incorporates constructs from habit theory, health action process approach (HAPA), and theory of planned behavior (TPB) is adopted to understand Iranian adolescents’ green purchasing behavior. Using a correlational-prospective design, the study recruited Iranian adolescents aged between 14 and 19 years (N = 2374, n = 1362 (57.4%) females, n = 1012 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Empirical research [ 43 ] verified that, in addition to attitudes, social norms, and perceived behavioural control, past experiences also significantly predict intentions to purchase natural products. Also, the findings revealed by Pakpour et al [ 44 ] demonstrated the direct effects of not only perceived behavioural control, subjective norms, and attitudes but also past behaviour on green product purchase intentions. Past behaviour towards the purchase of green apparel had an effect on the perception of the benefits of green apparel and, consequently, on the purchasing of apparel [ 45 ].…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 93%
“…Empirical research [ 43 ] verified that, in addition to attitudes, social norms, and perceived behavioural control, past experiences also significantly predict intentions to purchase natural products. Also, the findings revealed by Pakpour et al [ 44 ] demonstrated the direct effects of not only perceived behavioural control, subjective norms, and attitudes but also past behaviour on green product purchase intentions. Past behaviour towards the purchase of green apparel had an effect on the perception of the benefits of green apparel and, consequently, on the purchasing of apparel [ 45 ].…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 93%
“…Perceived behavioral control manifests how difficult or easy it is to perform a behavior [24,37] . Various studies have confirmed perceived behavioral control's significant role in predicting an individual's behavioral intention [37][38][39] . For the third antecedent, the subjective norm is described as the perception of general social pressure [36] regarding how behavior is viewed by references such as friends, parents, relatives, and colleagues [26,27] .…”
Section: Theory Of Planned Behavior (Tpb)mentioning
confidence: 96%
“…In addition, employees should be empowered and encouraged to operate their work in accordance with the organization’s green objectives [ 58 , 61 ]. As shown in Table 1 , the metrics of green healthcare are related to food, energy, water, waste, medical supplies, purchasing, and transportation, each of which requires the interests and efforts of all employees [ 20 , 56 , 57 , 62 ]. As such, the active participation of employees is essential for implementing successful green healthcare activities.…”
Section: Research Model and Hypotheses Developmentmentioning
confidence: 99%